Technical risk assessment techniques in Mineral Resource Management with special reference to the junior and small-scale mining sectors - Theart, H.F.J. (University of Pretoria, 2013)
Dissertation (MSc (Earth Science Management and Practice))--University of Pretoria, 2007.